MASJID DAN KONTROL SOSIAL: ANALISIS SOCIAL BOND THEORY - Naila Noerita Aini; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study analyzes the phenomenon of romantic relationships occurring in the corridor of Al-Furqon Mosque at Universitas Pendidikan Indonesia (UPI), which are considered to deviate from the mosque’s function as a place of worship. A descriptive qualitative method was used, with interviews involving members of the Mosque Prosperity Council (DKM), students, and local vendors as primary data sources, and literature review as secondary data. The findings indicate that this phenomenon arises due to visitors’ low ethical literacy and a corridor environment that enables such behavior. Analysis using Hirschi’s Social Bond Theory reveals that weak attachment, commitment, involvement, and belief in religious values are the main causes. DKM regulations are considered ineffective due to lack of supervision and ethical education. The study recommends strengthening written regulations, providing religious value education, and fostering collaboration between DKM, students, and the community to maintain the mosque’s sanctity. The implementation of these measures is expected to improve supervision and raise collective awareness, ensuring Masjid Al-Furqon functions effectively as a comfortable and respectful place of worship for all.